Indicators Of Investment Environment Attractiveness In Special Economic Zones - Mavlyanov Zafar Sahibovich (Zien Journals, 2026)
This article analyzes the key indicators used to assess the attractiveness of the investment environment in special economic zones. The attractiveness of the investment environment is an important factor for investors’ decision-making and is shaped by economic, institutional, legal, and infrastructural indicators. The article highlights the impact of factors such as tax and customs incentives, simplification of administrative procedures, development of transport and logistics infrastructure, labor potential, and legal stability on investment activity. Furthermore, mechanisms to enhance investment attractiveness are discussed based on the experiences of special economic zones in both developed and developing countries. The research results can be used to develop practical recommendations for the effective organization of special economic zones and improvement of the investment environment
Keywords: special economic zone; investment environment; investment attractiveness; tax incentives